2022
DOI: 10.1111/nyas.14857
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal music training enhances executive functions in children: Results of a randomized controlled trial

Abstract: Music training programs have shown mixed results on children's executive functions. The purpose of the present study was to evaluate the impact of a 10‐week multimodal music program with vocal development, bimanual coordination, and musical improvisation, on children's executive functions. We hypothesized that a 10‐week music program would enhance executive functions in working memory in 4‐ to 6‐year‐old children. Eighty‐four children were randomly assigned to a multimodal music program, an active control Lego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The antidote here is an RCT consisting of all the proper blinding procedures. However, in some cases when RCT design has been used in the first place, 26 there have been high numbers of dropout participants before and during the intervention, indicating that participants “vote with one's feet.” 51 , 52 So, we can argue that there is an important place for well‐designed studies that are not RCTs. Such studies would optimize intervention outcomes by building on the motivation of the participant rather than trying to suppress it.…”
Section: Introductionmentioning
confidence: 99%
“…The antidote here is an RCT consisting of all the proper blinding procedures. However, in some cases when RCT design has been used in the first place, 26 there have been high numbers of dropout participants before and during the intervention, indicating that participants “vote with one's feet.” 51 , 52 So, we can argue that there is an important place for well‐designed studies that are not RCTs. Such studies would optimize intervention outcomes by building on the motivation of the participant rather than trying to suppress it.…”
Section: Introductionmentioning
confidence: 99%
“…Guhn et al (2020) looked at young kids who were learning an instrument and found that their arithmetic exam scores were better if they had started studying an instrument before entering the fourth grade. The Music Spatial-Temporal Maths Program, according to Bugos et al (2022), had little impact on the arithmetic proficiency of second graders. The research's contradictory results may be explained by the kind of musical activities undertaken and the quantity of time spent on them.…”
Section: Numeracymentioning
confidence: 96%
“…Also, the ongoing everyday musicking by individual owners of a personal song was likely to promote greater emotional control, thereby contributing to the general reduction of interpersonal conflicts within a community. The evidence of such a mediative and regulatory role of music has been provided by numerous recent studies of the enhancing influence of music on the inhibitory control in children (Bolduc et al, 2021 ; Bugos et al, 2022 ; Hennessy et al, 2019 ; Joret et al, 2017 ; Moreno & Farzan, 2015 ).…”
Section: Summary Of Our Four-stage Modelmentioning
confidence: 99%